2015
DOI: 10.1371/journal.pone.0126117
|View full text |Cite
|
Sign up to set email alerts
|

The Glocal Forest

Abstract: Spatial ecological patterns reflect the underlying processes that shape the structure of species and communities. Mechanisms like intra- and inter-specific competition, dispersal and host-pathogen interactions can act over a wide range of scales. Yet, the inference of such processes from patterns is a challenging task. Here we call attention to a quite unexpected phenomenon in the extensively studied tropical forest at the Barro-Colorado Island (BCI): the spatial deployment of (almost) all tree species is stat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
(67 reference statements)
2
6
0
Order By: Relevance
“…Nevertheless, the quasi-collapse in the VMRs plot suggests a more radical insight: that the recruitment kernel of a species is proportional to i 0  , i.e., that there are correlations between the typical distance between a tree and its offspring (a "local" characteristics of the dynamics) and the overall abundance of this species in the foresta "global" feature. This conclusion is in agreement with another study that our recent study [30], supporting this "glocality" by implementing other point-pattern analyses.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, the quasi-collapse in the VMRs plot suggests a more radical insight: that the recruitment kernel of a species is proportional to i 0  , i.e., that there are correlations between the typical distance between a tree and its offspring (a "local" characteristics of the dynamics) and the overall abundance of this species in the foresta "global" feature. This conclusion is in agreement with another study that our recent study [30], supporting this "glocality" by implementing other point-pattern analyses.…”
Section: Resultssupporting
confidence: 93%
“…Following this result, we implemented here two versions of the VMR analysis: one is based on objective scales, the other utilizes the species specific scale i 0  . As seen in the results section, the VMR analysis seems to support the conclusions of [30], suggesting that spatial patterns of different species are becoming similar once the distances are normalized (for every species) by…”
Section: Methodssupporting
confidence: 67%
See 1 more Smart Citation
“…However, both studies did not consider plant interaction horizons and used species level co‐occurrences. Therefore, our present results are best compared to respective individual based work on the spatial distributions of temperate (Lawes et al 2008, Zhang et al 2009) and particularly tropical forest trees (Condit et al 2000, Baldeck et al 2013, Seri et al 2014, May et al 2015). These studies also returned a variety of spatial patterns in dependence on study site, taxon and species abundance but indicated a prevalence of intraspecific clustering.…”
Section: Discussionmentioning
confidence: 79%
“…Relying on the study of the g ( r ), double-cluster process has been proposed to explain the spatial distribution of some selected species [ 19 ]. The PCF and other statistical quantities (such as the nearest neighbour distribution) have been also studied in [ 40 ]. Finally, a few studies have pinpointed the relevance of neutral competition to generate non-trivial spatial patterns at the single-species level [ 41 43 ].…”
Section: Introductionmentioning
confidence: 99%